Sucesso da Tecnologia de Informação em Pequenas e Médias Empresas: Proposição Conceitual e a Percepção de Gestores. - Torres, Isabelle Vasconcelos (2009)
A wide-ranging research was made in scientific articles published in national and international literature about information technology (IT), models of successful information technology (SIT), success of projects, success of IT projects and IT implementation aiming the identification of facts considered success indicators to all stakeholders involved in the information technology implementation by the companies. Following the research, features were pointed as most used tools to measure SIT. Based on the studies of Gable et al. (2008), Sabherwal et al. (2006), Karlsen et al. (2005) and Dvir et al. and seeking factors present in the classic socio-technical four dimensions developed by Leavitt (1965) and set up recently in Palvia et al. (2001). Also, it was developed a survey model which was tested from a questionnaire answered by SMEs managers. The model considers the dimensions: people, organization, technology and tasks, as well as a fifth dimension called External Factors that is often current in the literature. This study brings in the identification of points of convergence e divergence between the literature researched and the managers perception of the SIT, concluding the SIT is a awareness of socio-technical nature, and it might be described as being a result of optimization of social and technical components which interact and induce during the IT development, use and maintenance. Another important conclusion is that is impossible to have a unique definition to SIT, considering the proof that it has a multidimensional nature, being its factors identified from a distinctive form, according to the point of view; in other words, each stakeholder involved in the implementation process has a peculiar rule to recognize the SIT from the implementation of the organizations. From the data collection, the survey model was revised and resized using the SME s manager s perception. It is strongly suggested that the research instrument be applied extensively in other contexts in order to fine-tune it for measuring STI in specific SMEs.